THE EFFECT OF FAMILY INVOLVEMENT IN COMPANY MANAGEMENT ON COMPANY PERFORMANCE - Annisa Marsela; Indrian Supheni; Sri Murni; Asri Diah Susanti; Rohwiyati (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This study aims to determine the effect of family involvement in company management on company performance. This study uses a purposive sampling technique to determine the research sample. This technique produces 380 research sample data. This study uses the Ordinary Least Square (OLS) method in analyzing hypotheses. The results of the study indicate that the involvement of family CEOs has no effect on company performance. Meanwhile, the involvement of family director’s has a positive effect on company performance. This research is limited by the sample company information used, so it is hoped that further research can add other sources of information related to family company ownership and or change the measurement of family businesses in analyzing family businesses or companies.